Laparoscopic Management of Unusual Presentation and Age of Xanthogranulomatous Cholecystitis, Case Report and Literature Review - AlSuwaydani , Saleh A; Alfehaid, Mohammed (International Journal of Innovative Research in Medical Science, 2021)
Background: Xanthogranulomatous cholecystitis XGC is a rare variant of Cholecystitis characterized by extensive inflammation and Fibrosis and associated with more complicated presentation like invading other organs and fistula formation. it could mimic Underlying malignancy like Gallbladder Cancer GBC. Challenges started by difficulty of diagnosis pre operatively due to multi factors include less threshold of diagnosis, which can lead to over treatment if GBC suspected. Gallstones plays major role in pathogenesis of most variant of Cholecystitis and can be trigger for GBC. Case presentation: we report 2 cases with different pre-operative course, both cases managed with laparoscopic cholecystectomy, and Histopathology showed Xanthogranulomatous cholecystitis XGC. Discussion: recent cases reported for XCG usually occurs in 5th and 6th decades and presented with multiple presentation and could be missed diagnosis, laboratory and radiological investigations can offer a limited diagnosis if not interpreted by expertise. Management can vary from simple laparoscopic cholecystectomy -as in our cases – and can extend to major en block resection.